2007
DOI: 10.1007/s11027-007-9103-8
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation and mitigation strategies in agriculture: an analysis of potential synergies

Abstract: Adaptation, Agriculture, Climate change impacts, Mitigation, Regional disparities, Synergies, Tradeoffs,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
151
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(156 citation statements)
references
References 52 publications
2
151
0
3
Order By: Relevance
“…Compared to the historical baseline, the 50% probability total grain yield by the 2070s is projected to increase 23-37% for RCP 4.5 and 35-71% for RCP 8.5 depending on the AEC, with CC showing the greatest absolute increase and CF showing greatest relative increase compare to baseline yields. Based on limited studies in the IPNW, yields of wheatbased systems are projected to benefit from climate change for most of this century, with the degree of benefit depending on RCP (Thomson et al, 2002;Rosenzweig and Tubiello, 2007;Stöckle et al, 2010). Although, the yield response to future temperature changes can be fairly uncertain (Asseng et al, 2015), the moderate current temperatures in the region and earlier crop maturity under future conditions will mitigate deleterious effects of temperature on crop yields.…”
Section: Yields and Crop Water Usementioning
confidence: 99%
See 1 more Smart Citation
“…Compared to the historical baseline, the 50% probability total grain yield by the 2070s is projected to increase 23-37% for RCP 4.5 and 35-71% for RCP 8.5 depending on the AEC, with CC showing the greatest absolute increase and CF showing greatest relative increase compare to baseline yields. Based on limited studies in the IPNW, yields of wheatbased systems are projected to benefit from climate change for most of this century, with the degree of benefit depending on RCP (Thomson et al, 2002;Rosenzweig and Tubiello, 2007;Stöckle et al, 2010). Although, the yield response to future temperature changes can be fairly uncertain (Asseng et al, 2015), the moderate current temperatures in the region and earlier crop maturity under future conditions will mitigate deleterious effects of temperature on crop yields.…”
Section: Yields and Crop Water Usementioning
confidence: 99%
“…One weakness of the study is the use of a single crop model for yield projections, although the CropSyst model has been used extensively in wheat studies in the IPNW (Pannkuk et al, 1998;Peralta and Stöckle, 2002;Stöckle et al, 2010; and around the world, Pala et al, 1996;Sommer et al, 2013;Donatelli et al, 2015;Holzkämper et al, 2015;O'Leary et al, 2015). Previous studies conducted with other models have also shown positive impacts of climate change in the region (Thomson et al, 2002;Rosenzweig and Tubiello, 2007). Furthermore, a study of winter wheat production in the IPNW using 5 well-established cropping system models calibrated for the region and downloaded weather from 14 GCMs also reported improved winter wheat yields throughout the century, with CropSyst consistently producing more conservative projections than the mean of the ensemble of the 5 crop models (Ahmed et al, under review).…”
Section: Aec Classification Based On Yield Percentilesmentioning
confidence: 99%
“…The actions of adjusting practices or adaptation strategies to extreme climate events can largely dominate the agricultural production (Smit and Skinner, 2002;Rosenzweig and Tubiello, 2007;Fosu-Mensah et al, 2012). Generally, local managers and farmers will design adaptation measures according to the crop exposure to adverse climatic hazards and past risk management experience.…”
Section: Effects and Improvement Potential Of The Adaptation In Northmentioning
confidence: 99%
“…Mitigation actions tend to focus on the energy, transport, and industry sectors, while the sectors most vulnerable to climate change and of concern to adaptation decision makers are usually agriculture, land use, forestry, and coastal zone management (Huq and Grubb 2007). However, there is certainly potential for overlap at the sectoral level; for example, adaptation policies in the agriculture, land use, and forestry sectors carry implications for CO 2 sequestration and avoid methane emissions (Dang and others 2003;Rozenweig and Tubiello 2007).…”
Section: Existing Work On Linking Mitigation and Adaptationmentioning
confidence: 99%